Quality and Microbiome Analysis of Pickled Swimming Crabs (Portunus trituberculatus) during Storage at Two Alternative Temperatures - Chen, Yu; Li, Peipei; Xu, Dan; Zhang, Xiaojun; Huang, Tao (Molecules (Basel, Switzerland), 2023)
The storage quality and microbiome analysis of pickled swimming crabs (Portunus trituberculatus) stored at 20 and 4 °C were investigated. It showed that samples stored at 4 °C had a longer shelf life, lower total viable count (TVC), pH, and total volatile base nitrogen (TVB-N) contents than those stored at 20 °C. The biogenic amine (BA) results demonstrated that tyramine (tyr), putrescine (put), and cadaverine (cad) were the dominant amines in all samples, and samples stored at 4 °C had lower BA contents. A microbiome analysis indicated that a salt–alcohol water mixture significantly inhibited the growth of Tenericutes. Firmicutes, Proteobacteria, Bacteroidetes, Acidobacteria, Actinobacteria, and Cyanobacteria were the dominant bacteria of stored pickled crabs, and storage at 4 °C significantly inhibited the growth of dominant bacteria, more than that of 20 °C. In conclusion, 4 °C storage guaranteed the quality of samples by inhibiting changes in biochemical properties and the growth of dominant bacteria, thereby prolonging its shelf life.